Analisis Pengaruh Interferensi Frekuensi Terhadap Kinerja Access Point Dengan Teknologi IEEE 802.11n - Suri Darmiantini; I Wayan Agus Arimbawa; Andy Hidayat Jatmika (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
Technologies that support wireless networks include WLAN (Wireless Local Area Network) and WPAN (Wireless Personal Area Network). One of the most widely used WLAN products today is IEEE 802.11n while the WPAN application is Bluetooth. Using the same frequency band in a coverage area can cause interference. Interference that occurs can be caused due to the use of 2 pieces of the same communication system, as well as different in a region. This study aims to determine how much influence interference has on the decline in the quality of a communication system with parameters measuring bandwidth, jitter, and packet loss. From the results of measurements and analysis shows that network quality is affected due to interference. Where if the network is free from interference around it, the network quality will be better, if the network experiences interference because using the same frequency band in the same coverage area can affect network quality such as reduced bandwidth value, increased jitter, and packet loss as well as channel usage and different channels. And the closer the distance of the access point that uses a different channel in a coverage area will cause the decreasing bandwidth value to increase the value of jitter and packet loss and vice versa. Keywords: interference, wireless, channel, bandwidth, jitter, packet loss.